Pengaruh Model Pembelajaran Numbered Head Together Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VIII SMP Negeri 2 Lintongnihuta Kabupaten Humbang Hasundutan Tahun Pembelajaran 2022/2024” - Willy Jonathan M. Purba; Senida Harefa; Robert K.A Simangunsong (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to determine the positive and significant influence of the Numbered Head Together model on the learning motivation of class students at SMP Negeri 2 Lintongnihuta Humbang Hasundutan district for the 2023/2024 academic year. The method used in this research is a quantitative method with a descriptive approach. The population of all class VIII students at SMP Negeri 2 Lintongnihuta for the 2023/2024 academic year is 207 people and a sample of 42 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 35 items. The results of data analysis show that there is a positive and significant influence of the Numbered Head Together model on the learning motivation of class students at SMP Negeri 2 Lintongnihuta Humbang Hasundutan district for the 2023/2024 academic year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.482 > rtable(a=0.05,n=42) = 0.304, thus it is known that there is a positive relationship between variable ,dk=n-2=40)= 2.021, thus there is a significant relationship between variable X and variable Y. 2) . b) Regression coefficient of determination test (r2) = 23.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=22, dk denominator=n-2=42-2=40) namely 12.07 > 1.51. Thus, the research hypothesis which states that there is a positive and significant influence of the Numbered Head Together learning Model on the learning motivation of class students at SMP Negeri 2 Lintongnihuta, Humbang Hasundutan district, for the 2023/2024 academic year is accepted.